Report on the World Current Account Discrepancy. (International Monetary Fund, 1987)
The IMF, in cooperation with other concerned organizations, set up a working party to investigate and improve the statistical procedures being used, and to recommend compilation procedures that would make nations' balance of payments statistics more consistent with one another. In addition to detailed explanations of its findings and recommendations, the Report contains extensive statistical appendices and 109 tables.